Consulting report - Natura Cosmeticos - improvement of consultant's experience - Coaguila Sutti, Tony Ronald; Cusipuma Frisancho, Mayra Carmen (Pontificia Universidad Católica del Perú, 2018)
Natura is a cosmetics company, which looks to merge cosmetics with personal relationships. The company is located in eight different countries, Peru, Mexico, Chile, Argentina, Bolivia, Brazil, Colombia, and France. The present consulting report focuses on Natura Peru. The company operates through direct sales, via door-to-door distribution. Therefore, the consultant is a pillar very important in the company. For this reason, the company looks to improve the consultants’ experience, which is the final goal of the consulting project. After the initial analysis of the company´s current situation, the key problem was that Natura has a suboptimal beauty consulting experience. This problem causes claims and represents unnecessary losses for the company. The operational and logistics area are the ones directly involved with the problem. The investigation focus is placed on the picking line, warehouse, and delivery process. The proposed solution addressed the problem in three aspects. Fist, stacking boxes according to the weight, by using a color-coding base on traffic lights. Second, using the XL box sparingly, delivering the small orders in the small or medium boxes and using a bag to deliver the merchandise. Finally, to employ a new cardboard with a layer of wax, in order to be able to protect the boxes from the rain. The proposal is expected to help the company to offer a better consultant experience and build a strong brand. An implementation plan, key success factors, and cost, were proposed to facilitate the application inside the company.

Natura es una compañía de cosméticos, que busca fusionar cosméticos con relaciones personales. La compañía está ubicada en ocho países diferentes, Perú, México, Chile, Argentina, Bolivia, Brasil, Colombia y Francia. El presente informe de consultoría se centrará en Natura Perú. La compañía opera a través de ventas directas, de distribución puerta a puerta. Las consultoras se convierten en la parte más importante de la compañía, por esta razón, la compañía quiere mejorar la experiencia de la consultora, que es el objetivo final del proyecto de consultoría. Después del análisis inicial de la situación actual de la compañía, el problema clave encontrado, fue que Natura tiene una experiencia de consultoría de belleza por debajo de lo óptimo. Este problema causa reclamos y representa pérdidas para la empresa. Las personas directamente involucradas con este problema son del área operativa y logística. La investigación se centra en la línea de picking, el almacén y el proceso de entrega. La solución propuesta abordó el problema en tres aspectos. Primero, apilar las cajas de acuerdo con el peso, utilizando una base de codificación con los colores del semáforo. Segundo, usar la caja XL con moderación, entregar las órdenes en cajas pequeñas o medianas y usar una bolsa para entregar los artículos publicitarios. Finalmente, utilizar una nueva caja cartón con una capa de cera para proteger las cajas de la lluvia. Se espera que la propuesta ayude a la compañía a ofrecer una mejor experiencia de consultoría y construir una marca sólida. Se propuso un plan de implementación, factores clave de éxito y costos para facilitar la aplicación dentro de la compañía.
Keywords: Administración de empresas; Ventas; Cosméticos--Industria y comercio--Perú; https://purl.org/pe-repo/ocde/ford#5.02.04